Investigation of Aliphatic Polyesters as Hydrogen Donor in Photoinitiated Free Radical Polymerization - Akat, Hakan; Ozkan, Melek; Saltan, Fehmi (Asian Journal of Chemistry, 2012)
In the present study, it has been demonstrated that polyesters were used as hydrogen donors in photoinitiated free radical polymerization of methyl methacrylate, N-methyl-2-pyrolidone and methacrylic acid by using one of the following photosensitizers; benzophenone, thioxanthone and 2-hydroxythioxanthone. The effect of molecular weight of poly(ethylene adipate) on the photoinitiation efficiency was investigated. The 2,2,6,6-tetramethylpiperidine-N-oxyl free radical attached polyesters were used as a model study. The synthesized polymer was characterized by 1H NMR, FTIR and gel permeation chromatography.